Public health emergency preparedness: a framework to promote resilience - Khan, Yasmin; O’Sullivan, Tracey; Brown, Adalsteinn; Tracey, Shannon; Gibson, Jennifer; Généreux, Mélissa; Henry, Bonnie; Schwartz, Brian (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Emergencies and disasters impact population health. Despite the importance of upstream readiness, a persistent challenge for public health practitioners is defining what it means to be prepared. There is a knowledge gap in that existing frameworks lack consideration for complexity relevant to health systems and the emergency context. The objective of this study is to describe the essential elements of a resilient public health system and how the elements interact as a complex adaptive system. Methods This study used a qualitative design employing the Structured Interview Matrix facilitation technique in six focus groups across Canada. Focus group participants were practitioners from public health and related sectors. Data collection generated qualitative data on the essential elements, and interactions between elements, for a resilient public health system. Data analysis employed qualitative content analysis and the lens of complexity theory to account for the complex nature of public health emergency preparedness (PHEP). The unit of study was the local/regional public health agency. Ethics and values were considered in the development of the framework. Results A total of 130 participants attended the six focus groups. Urban, urban-rural and rural regions from across Canada participated and focus group size ranged from 15 to 33 across the six sites. Eleven elements emerged from the data; these included one cross-cutting element (Governance and leadership) and 10 distinct but interlinked elements. The essential elements define a conceptual framework for PHEP. The framework was refined to ensure practice and policy relevance for local/regional public health agencies; the framework has ethics and values at its core. Conclusions This framework describes the complexity of the system yet moves beyond description to use tenets of complexity to support building resilience. This applied public health framework for local/regional public health agencies is empirically-derived and theoretically-informed and represents a complex adaptive systems approach to upstream readiness for PHEP.